1990
DOI: 10.2105/ajph.80.9.1101
|View full text |Cite
|
Sign up to set email alerts
|

The effects of workplace health promotion on absenteeism and employment costs in a large industrial population.

Abstract: We evaluated the impact of a comprehensive workplace health promotion program on absences among full-time employees in a large, multi-location, diversified industrial company. A pretest-posttest control group design was used to study 41 intervention sites and 19 control sites with 29,315 and 14,573 hourly employees, respectively. Blue-collar employees at intervention sites experienced an 14.0 percent decline in disability days over two years versus a 5.8 percent decline at control sites. This resulted in a net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0
8

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(109 citation statements)
references
References 30 publications
2
93
0
8
Order By: Relevance
“…Reading the title or abstracts or both resulted in the exclusion of 177 publications. After the whole text of the rest of the publications was read, another 20 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) had to be excluded. Most of the studies were excluded because they did not involve a physical activity program at a worksite or did not evaluate the effect on work-related outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Reading the title or abstracts or both resulted in the exclusion of 177 publications. After the whole text of the rest of the publications was read, another 20 (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38) had to be excluded. Most of the studies were excluded because they did not involve a physical activity program at a worksite or did not evaluate the effect on work-related outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In line with the association between well-being and employer outcomes, studies have found that overall well-being and its subdomains can be improved through individual interventions that target these elements of well-being, [30][31][32][33] and well-being-related interventions have been linked directly to improved employer outcomes such as health care cost and utilization, [34][35][36] disability leave, 37,38 absenteeism, 31,39 and presenteeism, 40 as well as employee turnover intentions. 41,42 Although it has been established that well-being improvement is attainable through individual intervention, no study to date has examined the connection between overall wellbeing change and outcomes change.…”
Section: Introductionmentioning
confidence: 90%
“…[603][604][605] The fourth study by Hammer et al 606 investigated couples' or individuals' use of alternative work arrangements and dependent care support.…”
Section: Hrm Practice/interventionmentioning
confidence: 99%